Euphorbia hirta Leaves Extracts for Removal of Warts and Skin Diseases - Kripa, N.; Kishore Kanna, R. (Journal of Natural Remedies, 2022)
Euphorbia hirta is a a medicinal plant which is been widely used from olden days as a herbal medicine for various purposes for mankind. Our country is known for its medical and Ayurvedic treatments. Various parts of the plant is been used for various uses, and here the leaves are been used for the treatment of warts and skin diseases. Questionnaire was prepared and the feedback was collected before the usage of this medicinal plant. The latex or the sap of the plant was collected from Euphorbia hirta and it has been used for the treatment. After the completion of the treatment again questionnaire was given and the feedback was collected for the group of people. This research describes about the medicinal properties, the days of treatment, the feedback and the other important aspects of Euphorbia hirta. The research enlightens on how efficient the leaf extracts of Euphorbia hirta totally irradiated the warts and the fungal diseases totally without any pain and side effects. Moreover, the availability of the leaves are abundant and easily available, hence economical. There are many medicinal plants around us like this each having its own chemical composition which can be used in our daily life without any side effects instead of going for synthetic drugs.